PERBANDINGAN HASIL BELAJAR GEOGRAFI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DAN TIPE NHT BERDASARKAN KEMAMPUAN AWAL SISWA - Duwi Febrilia; Pargito Pargito; sugeng widodo (JPG (Jurnal Penelitian Geografi), 2013)
This study aims to compare the results of learning geography through cooperative learning model type and type TGT NHT students of SMAN 12 Bandar Lampung Year 2012/2013. The method used in this study is quasi-experimental methods (quasi experimental design) with a population of students of class XI IPS SMA 12 Bandar Lampung totaling 124 students were then sampled as many as 62 students. Analysis of the data using paired samples t-test. Based on the data analysis, the results showed that: 1. There is a difference in learning outcomes at the beginning of high-ability students who use learning model TGT (mean = 83.85) using the model pembelajarn NHT (mean = 68.85). 2. There is a difference in learning outcomes in students with low initial TGT using learning model (mean = 72.78) using the model pembelajarn NHT (mean = 58.61). 3. Learning outcomes at the beginning of high-ability students and low initial capability model TGT higher learning (high = 83.85, low = 72.78) than the average student learning outcomes Geography NHT model (high = 70.00, low = 58.61).